Computers in Education and Education in Computer Science - José Luis SIERRA-RODRÍGUEZ; Francisco José GARCÍA PEÑALVO (Ediciones Universidad de Salamanca, 2015)
Selection of the extended papers related to Computers in Education and Computer Science Education topics presented at the sixteenth edition of the International Symposium on Computers in Education (SIIE 2014), held between 12 and 14 November 2014 in Logroño, La Ri-oja, Spain.